An application board to the Atmega32 microcontroller board [electronic resource] - Mohd. Hafiz Mohamad Nor, 1989-; Zuraimi Yahya, supervisor (2012)
Project Paper (Sarjana Muda Kejuruteraan (Komputer)) - Universiti Teknologi Malaysia, 2012